Farmer-Herder Conflict in the Middle Belt and Threat to Food Security in Nigeria: Exhuming Evidences from The Benue State Experience - NNAETO, JAPHET (Governance and Society Review, 2025)
The Middle Belt, led by Benue state is regarded as the food basket of Nigeria due to its contribution to food production in Nigeria. Production of sufficient food for local and transnational consumption remains a major source of diet and foreign earning for a country. The near intractable farmers-herders conflict in Middle Belt, particularly in Benue State, spanning several years has effectively jeopardized food security for both local consumption and export. Many farmers now avoid going to farm out of fear of possible attack that often results to death, rape, maiming and destruction of cash crops, precipice for food insecurity. The study aimed to identify the causes, consequences and solution to the perennial farmers-herders conflict in the region. It employed secondary data and anchored inEco-violence theory by Homer-Dixon. Documentary evidences revealedinter alia that quest to grab lands for grazing of cattle is the fundamental reason for herders’ incessant attacks on the people and farms of Middle Belt, particularly Benue State. The widespread destruction of life and property, permanent maiming of citizens,the deep-seated mutual fear and discord, clashes and the discernible destabilization of Nigeria caused by these conflicts, underscore the urgent need for intervention. The study recommends measures such as, introduction of modern ranching and immediate and sustainable multi-dimensional action to disarm the conflicting parties.